A Review of the Effects of Social Loafing on Firm’s Performance: Organizational behavior - Yusuf, Yahaya; Sanusi, Fauziyya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This paper examines the effect of social loafing on overall firm performance. It reviewed numerous research articles on social loafing and a conceptual model was developed to assess the relationship between the independent and the dependent variables. The review discovered that negative effects of social loafing on work group performance have an adverse effect on the productivity and goal accomplishment of the firm. Therefore, the study recommends that in order to improve employee performance and achieve organizational goals and objectives, social loafing can be reduced by minimizing free riding, encouraging team loyalty and assigning of distinct responsibilities for each team member. This will in turn encourage originality and creativity, which will motivate the employees to put in more effort to work, thereby enhancing the achievement of organizational aims and objectives